Enhancing intrinsic thermal conductivities of epoxy resins by introducing biphenyl mesogen-containing liquid crystalline co-curing agents. Issue 42 (18th October 2022) - Dang, Jinjin; Zhang, Junliang; Li, Mukun; Dang, Lin; Gu, Junwei
Abstract : Epoxy resins were prepared with an enhanced intrinsic thermal conductivity of 0.42 W (m K) −1 using a biphenyl mesogen-containing co-curing agent. Abstract : In this work, a biphenyl liquid crystalline small molecule (BLCM) containing flexible units was synthesized via a one-step condensation reaction of 4, 4′-dihydroxybiphenyl (BP) and 1, 6′-dibromohexene. Then, the commercially available bisphenol A epoxy (E-51) was used as a matrix, 4, 4′-diaminodiphenylmethane (DDM) as a curing agent, and the BLCM as a co-curing agent to prepare highly intrinsic thermally conductive liquid crystalline epoxy resins (LCER) by a casting method. Nuclear magnetic resonance spectroscopy, high-resolution mass spectroscopy, and Fourier transform infrared spectroscopy demonstrated that the BLCM with a designed structure was synthesized successfully. Wide-angle X-ray diffraction, small-angle X-ray scattering, and polarized light microscopy proved that the inter-stacking of biphenyl mesogens promoted the formation of locally ordered regions in the LCER. Meanwhile, the ordered structure of the LCER was enhanced with an increase of the BLCM mass fraction, resulting in the higher intrinsic thermal conductivity. When the mass fraction of the BLCM was 60% of E-51 (LCER3), the thermal conductivity ( λ ) of LCER3 was 0.42 W (m K) −1, which was 2.1 times that of an epoxy resin cured with DDM only (LCER0, λ was 0.20 W (m K) −1 ). Besides, LCER3 presented a high heat resistance index ( T HRI ) of 176.8 °C, elastic modulus of 4.8 GPa, and hardness of 0.32 GPa, which was also higher than LCER0 with a T HRI of 172.2 °C, elastic modulus of 3.7 GPa, and hardness of 0.27 GPa.